NURSING INTERVENTIONS IN MANAGEMENT OF COVID-19-RELATED DELIRIUM IN INTENSIVE CARE UNITS: LITERATURE REVIEW - Emine KAPLAN SERİN (Rojan GÜMÜŞ, 2021)
Development of delirium is highly probable in Covid-19 patients and its management is much more difficult than in other diseases. Nurses have important roles in delirium management that may develop in covid-19 patients. The aim of this paper was to review the literature regarding non-pharmacological interventions in intensive care units (ICUs) to prevent the delirium in Covid-19 patients. A literture review was used. The terms used in the literature search were 'intensive care' or 'critical care' including their abbreviations, as well as 'delirium,' 'intervention,' 'approach,' 'nursing' or 'non-pharmacologic' or 'treat' or 'management' or 'prevention' and 'Covid-19' with Turkish and English words. Literature was scanned using keywords based on the Medical Subjects Headings (MeSH) and Embase Tree (EMTREE) from the databases of Cochrane, CINAHL, PsyInfo, PubMed, and EMBASE.A total of 63 studies were included in the review. In this paper, it was found that non-pharmacological interventions had an important place in delirium management; however, the transmission way of Covid-19 via droplets prevents many non-pharmacological attempts. First and fore-most among these interventions is the termination of the sedating drug, preventing isolation, ensuring that the patient spends time with visitors, and weaning from mechanical ventilation. Covid-19 patients, latest technology can be used for help prevent social isolation. Based on the findings of this literature review, we recommend a patient-centered approach in the management of delirium in Covid-19 patients and a revision of current strategies in accordance with the profiles of the patient and the disease. To raise awareness in interventions for delirium syndrome that may cause in covid 19 disease for nurses.